2002
DOI: 10.1074/jbc.m109113200
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 16 E7 Binds to E2F1 and Activates E2F1-driven Transcription in a Retinoblastoma Protein-independent Manner

Abstract: The human papillomavirus (HPV) E7 oncoprotein can immortalize primary human cells and induce tumor formation. These properties of E7 depend on its ability to inhibit the activity of retinoblastoma protein (pRB), which in turn affects E2F function. E2F proteins control the expression of genes involved in differentiation, development, cell proliferation, and apoptosis. By using genetic and biochemical approaches, the present study shows that E7 binds to E2F1 in vivo and in vitro and that both proteins co-localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 69 publications
6
87
0
4
Order By: Relevance
“…Notably, a recent study has shown that E7 can also interact with E2F-1 in a pRbindependent fashion, thereby augmenting its proapoptotic activity. In this constellation, expression of both proteins in pRb-negative cells resulted in stronger apoptosis than with E2F-1 alone (Hwang et al, 2002). These data are related to our previous observation that pRb degradation and apoptosis occurred only in E7 oncogene-expressing cells, but not in their E6-positive counterparts (Finzer et al, 2001).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Notably, a recent study has shown that E7 can also interact with E2F-1 in a pRbindependent fashion, thereby augmenting its proapoptotic activity. In this constellation, expression of both proteins in pRb-negative cells resulted in stronger apoptosis than with E2F-1 alone (Hwang et al, 2002). These data are related to our previous observation that pRb degradation and apoptosis occurred only in E7 oncogene-expressing cells, but not in their E6-positive counterparts (Finzer et al, 2001).…”
Section: Discussionsupporting
confidence: 76%
“…In cervical carcinomas, which represent the second most frequent gynecological malignancy worldwide (Pisani et al, 2002), pRb is deregulated by the human papillomavirus (HPV) E7 oncogene, which results in the unscheduled transcriptional activation of E2F target genes (Dyson et al, 1989;Hwang et al, 2002). Since malignant growth arises from the simultaneous occurrence of deregulated cell proliferation and suppressed apoptotic signals (Green and Evan, 2002), it is striking that inhibitors of the histone deacetylase (HDAC) can efficiently revert both of these pathways in HPV-positive cancer cells (Finzer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the level of E2F1 protein and its activity as determined by c-Myc expression level were reduced upon 2-DG treatment (Fig. 3A), most likely because of the depletion of E7, which has been shown to activate E2F1 either directly (38) or through inactivation of Rb (39). Therefore, the status of these factors is as expected in HeLa cells where E6/E7 proteins were depleted.…”
Section: Repression Of Hpv Early Gene Expression By 2-dg Treatment Hmentioning
confidence: 99%
“…This effectively removes one of the main nodes of cell-cycle regulation at this point and facilitates unscheduled progression into S-phase. This is potentiated by the direct binding of E7 to E2F1 with consequent activation of E2F1-drive transcription (Hwang et al, 2002). The role of pRb is not limited to the G1/S boundary of the cell cycle.…”
mentioning
confidence: 99%